ANTIMICROBIAL ACTIVITY OF SURFACTANCES OF BACTERIA NOCARDIA, RHODOCOCCUS AND ACINETOBACTER GENERA - Pirog Т.P.; Kliuchka І.V.; Lutsai D.А.; Kliuchka, L.V.; Skrotska, O.I. (World of Medicine and Biology, 2021)
It was found that the minimum inhibitory concentrations against bacteria and yeast of Acinetobacter calcoaceticus IMV B-7241, Rhodococcus erythropolis IMV Ac-5017 and Nocardia vaccinii IMV B-7405 surfactants, synthesized on traditional substrates, were 9–120 μg/ml and were within the limits defined for the surfactants known in the world. It was for the first time established that surfactants synthesized by the study strains on wastes of biodiesel production and fried sunflower oil were characterized by high antimicrobial activity against bacteria and yeast (minimum inhibitory concentrations 0.45–120 and 1.9–142 μg/ml respectively). It was found that the added of both live and inactivated Escherichia coli ІEM-1 and Bacillus subtilis BT-2 cells in R. erythropolis IMV Ac-5017 and N. vaccinii IMV B-7405 medium cultivation was accompanied by synthesis of surfactants, minimum inhibitory concentrations of which were several times lower than those showed for surfactants synthesized without competitive microorganisms. The obtained results indicate the possibility of using the studied surfactants as effective antimicrobial agents.